Optical and electrical characterization of defects in zinc oxide thin films grown by atomic layer deposition - Krajewski, Tomasz A.; Łuka, Grzegorz; Wachnicki, Łukasz; Jakieła, Rafał; Witkowski, Bartłomiej; Guziewicz, Elżbieta; Godlewski, Marek; Huby, Nolwenn; Tallarida, Grazia (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In the present paper, we discuss the influence of point defects on electrical and optical characteristics of ZnO thin films grown by the atomic layer deposition (ALD) method. The films were grown on glass substrates at low temperature (100–200 °C). We used diethylzinc (DEZn) and deionized water as precursors. Room temperature photoluminescence (RT PL) spectra, secondary ion mass spectroscopy (SIMS), electron dispersive X-ray (EDX) analysis and Hall effect measurements were made for as-grown ZnO layers and for the annealed ones (in air at 300 and 400 °C as well as in N2 atmosphere at 400 °C). The air-annealed ZnO films reveal a substantial reduction of a carrier concentration (up to 4 orders of magnitude – from 1019 to 1015 cm–3) combined with changes in intensity of the defect-related luminescence bands. PL related to deep defects is shifted towards the lower energy range (red light emission) after annealing (in air and nitrogen-rich conditions).
Optica Applicata, Vol. 39, 2009, nr 4, s. 865-874
Keywords: optyka; zinc oxide; atomic layer deposition (ALD); electrical properties; photoluminescence